2020
DOI: 10.1038/s41586-020-2632-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterotypic cell–cell communication regulates glandular stem cell multipotency

Abstract: Author contributions A.C., S.L. and C.B. designed the experiments and performed data analysis. A.C. and S.L. performed most of the biological experiments. E.T. performed the experiments and data analysis on prostate glands. A.Sifrim., M.M., Y.S., J.V.H. and T.V. performed the bioinformatic analysis. A.D. and G.B. provided technical help. C.D. performed FACS experiments. N.D. provided technical help with single-cell RNA sequencing. A.C., S.L., M.F., A.W. and A.V.K. performed immunostainings, blocking antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 69 publications
1
61
0
Order By: Relevance
“…Further, either stimulating the TNF pathway or blocking Notch, Wnt and epidermal growth factor receptor (EGFR) signalling inhibits BC multipotency, which could be induced by LC ablation. 44 Together, these results support the notion that signalling communication between the glandular cells is critical to maintaining their lineage identity and restriction to mammary gland stem cells. Interestingly, a comparison of the wound repair processes following LC-specific ablation in four different glands-mammary gland, sweat gland, salivary gland and prostate gland-showed that, in general, unipotent progenitor cells within one lineage, for example LC, respond with the most significant improvement of proliferation rate.…”
Section: Mammary Glandsupporting
confidence: 71%
See 3 more Smart Citations
“…Further, either stimulating the TNF pathway or blocking Notch, Wnt and epidermal growth factor receptor (EGFR) signalling inhibits BC multipotency, which could be induced by LC ablation. 44 Together, these results support the notion that signalling communication between the glandular cells is critical to maintaining their lineage identity and restriction to mammary gland stem cells. Interestingly, a comparison of the wound repair processes following LC-specific ablation in four different glands-mammary gland, sweat gland, salivary gland and prostate gland-showed that, in general, unipotent progenitor cells within one lineage, for example LC, respond with the most significant improvement of proliferation rate.…”
Section: Mammary Glandsupporting
confidence: 71%
“…It has been suggested, based on prediction of ligand‐receptor pairs from single‐cell data, that TNF secreted by LCs in the mammary gland may restrict multipotency under normal conditions; therefore, it is likely that when nearby LCs are injured or ablated, loss of TNF may allow BC activation. Further, either stimulating the TNF pathway or blocking Notch, Wnt and epidermal growth factor receptor (EGFR) signalling inhibits BC multipotency, which could be induced by LC ablation 44 . Together, these results support the notion that signalling communication between the glandular cells is critical to maintaining their lineage identity and restriction to mammary gland stem cells.…”
Section: Glandular Wound Repairmentioning
confidence: 57%
See 2 more Smart Citations
“…To extrapolate information from underlying transcriptional networks, previous studies have employed several strategies to link cellular and molecular states to mammary epithelial identity. For example, combining flow cytometric isolation with functional cellular markers has improved our understanding of the dynamics of lineage commitment, differentiation processes and mammary tissue development [5,[14][15][16][17]. More recently, single-cell sequencing strategies have enabled the interpretation of contiguous cellular cues and epithelial lineage dynamics in the developing mammary gland [8,15,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%